GAMBARAN PENYAKIT DEMAM BERDARAH DENGUE DI RUMAH SAKIT UMUM LUBUK PAKAM - Yessi Sundari (Journal of Natural Sciences, 2020)
DBD is a disease caused by the dengue virus which is transmitted through mosquito bites and reduces the platelet count in the sufferer. This study aims to determine the medical records of dengue hemorrhagic fever at Lubuk Pakam General Hospital. This type of research is descriptive. Data collection methods were medical records for all DHF patients from 2005 to 2009 at Lubuk Pakam General Hospital. Then the medical record data are grouped by age, sex and occupation. Based on the results of the study, it was found that the number of DHF sufferers from 2005 to 2009 increased in the 21-56 year age group with all male sex and work as entrepreneurs. This is due to a narrower environment, increasing population, and inadequate living quarters with no good air ventilation, so that the spread of dengue is increasing.